Carbonic anhydrase activity of dinuclear CuII complexes with patellamide model ligands - Comba, Peter; Gahan, Lawrence R.; Hanson, Graeme R.; Maeder, Marcel; Westphal, Michael (Dalton transactions, 2014)
The dicopper(II) complexes of six pseudo-octapeptides, synthetic analogues of ascidiacyclamide and the patellamides, found in ascidians of the Pacific and Indian Oceans, are shown to be efficient carbonic anhydrase model complexes with kcat up to 7.3 × 103 s−1 (uncatalyzed: 3.7 × 10−2 s−1; enzyme-catalyzed: 2 × 105-1.4 × 106 s−1) and a turnover number (TON) of at least 1700, limited only by the experimental conditions used. So far, no copper-based natural carbonic anhydrases are known, no faster model systems have been described and the biological role of the patellamide macrocycles is so far unknown. The observed CO2 hydration rates depend on the configuration of the isopropyl side chains of the pseudo-octapeptide scaffold, and the naturally observed R*,S*,R*,S* geometry is shown to lead to more efficient catalysts than the S*,S*,S*,S* isomers. The catalytic efficiency also depends on the heterocyclic donor groups of the pseudo-octapeptides. Interestingly, the dicopper(II) complex of the ligand with four imidazole groups is a more efficient catalyst than that of the close analogue of ascidiacyclamide with two thiazole and two oxazoline rings. The experimental observations indicate that the nucleophilic attack of a CuII-coordinated hydroxide at the CO2 carbon center is rate determining, i.e. formation of the catalyst-CO2 adduct and release of carbonate/bicarbonate are relatively fast processes.